Brand Awareness and Country Image of Nepali Customers - Rai, Arjun (Journal of Emerging Management Studies, 2025)
Purpose – The main purposes of this research are to investigate the brand awareness and country image of Nepali consumers while using products or services. Design/methodology/approach – The survey was conducted to 100 respondents who were the government officials of the Ministry of Industry, Commerce and Supplies and Department of Industry. Descriptive statistics and Chi-Square test were used to analyze the collected data. The respondents who always check brands and always care about food brands were strongly associated. Those who care brands of Nepal’s food products have association with who care brands of Indian food products. Findings – The results of this research provide evidence that Nepali customers are highly aware about brands and mostly prefer foreign brands, and the Nepali market is dominated by foreign brands. Conclusion – These results suggest that foreign brands hold significant influence in Nepali market, and that country image plays an important role in shaping consumer behavior in Nepal. To strengthen the position of domestic products or services, policymakers and firms/companies need to invest in effective branding strategies and build stronger trust and recognition among Nepali consumers. Originality/value – This research adds new insights to the field by examining how awareness creates the image in the context of Nepali consumers brand awareness.